KOSTI Surabaya as a counterculture against the foreign culture in the era of generation 4.0 - Salmatian Safiuddin; Dewi Atikah (SIMULACRA: JURNAL SOSIOLOGI, 2020)
Indonesian Old Bicycle Community or Komunitas Sepeda Tua Indonesia (KOSTI) of Surabaya is a subculture consisting of old bicycle lovers in Surabaya. This qualitative study aims to clarify and strengthen the idea of Internet as a resource and media for the development of subcultures, to investigate online and offline activities of KOSTI Surabaya, and to promote further research on the diversity of subcultures like KOSTI Surabaya following the development of generation 4.0 trend. The researchers collected data through in-depth interviews and observation to the community members. The result indicates that KOSTI Surabaya promotes and maintains the local and Indonesian culture through offline and online communication. This present study can support the conceptualization of subculture in the digital era. This community helps young generations to put Indonesian important values and norms into practice through their lifestyle, such as to build a good relationship, kinship, brotherhood, to create a good harmony in life. In addition, this community becomes a media to foster and maintain our local culture. KOSTI Surabaya is the resistance against the modern culture which makes this community as counter culture against foreign culture challenges. Not only the use of a means of transportation but also of the nature of individualist that starts to embrace most of Indonesian people in urban areas.